2018
DOI: 10.1021/acsbiomaterials.8b00178
|View full text |Cite
|
Sign up to set email alerts
|

Customizing the Shape and Microenvironment Biochemistry of Biocompatible Macroscopic Plant-Derived Cellulose Scaffolds

Abstract: Plant-derived cellulose scaffolds constitute a highly viable and interesting biomaterial. They retain a high flexibility in shape and structure, present the ability to tune surface biochemistry, display a high degree of biocompatibility, exhibit vascularization, and are widely available and easily produced. What is also immediately clear is that pre-existing cellulose structures in plants can also provide candidates for specific tissue engineering applications. Here, we report a new preparation and fabrication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(135 citation statements)
references
References 58 publications
(159 reference statements)
6
118
0
Order By: Relevance
“…In addition, a large number of cell nuclei was observed around the cellulose pores as well as inside the scaffold pores ( Figures 1D and E). This is consistent with previous studies which showed that various types of cells successfully adhered and proliferated onto plant-derived cellulose scaffolds [14], [16]. Moreover, similarly to one of our previous study [14], we observed that the diameter of the scaffold individual pores was about 154 µm, with the majority of the pores being between 100 and 200 µm ( Figure 2).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In addition, a large number of cell nuclei was observed around the cellulose pores as well as inside the scaffold pores ( Figures 1D and E). This is consistent with previous studies which showed that various types of cells successfully adhered and proliferated onto plant-derived cellulose scaffolds [14], [16]. Moreover, similarly to one of our previous study [14], we observed that the diameter of the scaffold individual pores was about 154 µm, with the majority of the pores being between 100 and 200 µm ( Figure 2).…”
Section: Discussionsupporting
confidence: 93%
“…They were then extensively washed with deionized water before permeabilizing the cells with a Triton-X 100 solution (ThermoFisher) for 5 min, and washed again with PBS. Staining of the scaffolds was carried out as previously described [14], [16]. Briefly, the scaffolds were incubated in 1% periodic acid (Sigma-Aldrich) for 40 min.…”
Section: Pore Size Measurements and Cell Distribution Analysis Using mentioning
confidence: 99%
See 3 more Smart Citations